Norway's Chairship Arctic Council 2023 - 2025 (Norwegian Ministry of Foreign Affairs, 2023)
The Arctic Council is the leading intergovernmental forum for Arctic issues. The overall objective for Norway’s chairship of the Council will be to promote stability and constructive cooperation. We will focus on the core issues the Council deals with, including impacts of climate change, sustainable development, and efforts to enhance the well-being of people living in the region. Norway will continue to support ongoing activities and projects run by the Council’s six working groups and its expert groups. Our national priorities are based on the first Arctic Council Strategic Plan, which was adopted in Reykjavik in 2021. Through four priority topics: the oceans; climate and environment; sustainable economic development; and people in the north, we will continue to pursue the long-term approach taken by the Council in its important efforts to ensure a vibrant and sustainable Arctic region. A mid-term review of the Strategic Plan is to be carried out in 2025.